Characteristics of workers and their preferences to work from home (WFH) - Roslinah Mahmud; Lim, Fui Yee Beatrice; Khairul Hanim Pazim; Rasid Mail; Kasim Mansur; Borhan Abdullah; Rostika Petrus Boroh (Asian Scholars Network, 2020)
COVID-19 has contributed to drastic changes in labour market, such as work and how to do work. A flexible work arrangement encourages employees to work from home (WFH) among other alternatives during the crisis. To curb Covid-19 in Malaysia, the Government imposed Movement Control Order from 18 March 2020 until 9 June 2020. The Movement Control Order has halted all non-essential economic activities in the country. The restrictions also forced the temporary closure of schools, higher education institutions (HEIs) and all government and private premises. Instantaneous, workers were forced to work from home. The main objective of this study is to explore the demographics characteristics that affect the preferences to WFH among staff at Faculty Business, Economics and Accountancy (FBEA), Universiti Malaysia Sabah during the post-Covid-19. This study used primary data based on a structured questionnaire to find out the factors. The findings revealed that demographics characteristics such as marital status, children and productivity influence the decision to WFH.